Language and its limits - Gallerani Cutter, João Vergílio (Estudios de Filosofía, 2008)
I do not want to give the impression that I will attempt an approximation between the first and the second Wittgenstein that erases such fundamental differences as that. However, I must then clarify that it will be my intention to speak of the existence of "limits" of language in a sense that can be assimilated by those who accept the basic lines of argumentation of Philosophical Investigations. More exactly, I will try to redefine those limits in terms that are fully compatible with Wittgenstein's mature philosophy. Associated with this new definition of the notion of limit, I believe that a new conception of the Mystical will emerge, and a very particular kind of "negative theology", which I will try to define more exactly in the final part of my presentation. [Fragment]